Exploring risk containment among Big 4 firms through credit derivatives. (1st January 2014) - Lin, Ping; Zhang, Sanjian Bill; Zhang, Gaiyan
We define risk containment in this study as the practice of retaining or attracting low business risk clients and dropping high business risk clients for revenue growth and litigation minimisation. We conduct a comprehensive study of the risk containment by the Big–4 accounting firms based on two market measures: (a) credit default swap (CDS) spread and (b) delisting ratios of their clients. We predict that the average risk of one Big–4 accounting firm's client portfolio is lower than that of the other three Big–4 firms. Results from a sample in 2002–2007 lend support to our prediction and are consistent with the notion that one Big–4 firm has better risk management practices than others. Further robustness tests still generate similar results. We further test our hypothesis with the delisting percentage of the Big–4 clients. The diverging trend after 2006 is consistent with our prediction too.